Crucial images in the presentation of a Kurdish national identity heroes and patriots, traitors and foes - Strohmeier, Martin (Social, economic, and political studies of the Middle East and Asia, 2003)
This book deals with the discourse on Kurdishness and the development of the Kurdish national movement from its inception at the end of the 19th century to the late 1930's. The first part examines the efforts of aspiring Kurdish leaders, mainly through newspapers, to "awaken" their fellow Kurds to the necessity and benefits of the Kurdish cause. Part two deals with the rise of a Kurdish movement in exile, mainly in Syria, and analyzes various aspects of cultural nation-building as mirrored in Kurdish publications. Part three focuses on the effort of a prominent Kurdish nationalist to promote Kurdishness in a little-known novel written in German. The book includes an annex with translations from Ottoman and Turkish sources, illustrations, and an index.